PENGARUH INSENTIF TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS KELAUTAN DAN PERIKANAN KABUPATEN KUTAI TIMUR - Budi Harsono (ADMINISTRASI PUBLIK, 2018)
This study is intended to determine the effect of incentives on employee morale in the Department of Marine and Fisheries of East Kutai Regency, therefore the researchers to formulate hypotheses "Allegedly incentives have an impact on employee morale Marine and Fisheries Agency of East Kutai Regency".The timing of the research was conducted in late December 2015 to April 2016 for 4 (four) months. The research method in this study is quantitative, the data obtained through direct observation to the field, interviews and distributing questionnaires to the speakers with a sample size of 20 (twenty) of respondents.Based on the calculation of Product Moment Correlation is known there is a correlation between the incentive to employee morale with the number 0.756. This figure is interpreted as a strong correlation between the incentive to employee morale.While testing the hypothesis generating empirical rxy figure of 0.756 where r xy table for N = 20 (with a 95% confidence level) is 0.444, then the empirical rxy> r xy table. Thus it can be said that there is a positive relationship between the variable incentive (X) and variable morale (Y) employees at the Department of Marine and Fisheries of East Kutai.